2003
DOI: 10.1007/s00572-003-0221-1
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi associated with Araucaria angustifolia (Bert.) O. Ktze

Abstract: Specimens of Araucaria angustifolia from a native forest reserve and a reforested area in the State Park of Campos do Jordão were studied to determine the number and diversity of spore populations of arbuscular mycorrhizal fungi (AMF) and root colonization. Six randomly chosen plots (planted with 8- to 12-year-old plants) were delimited, four in the native forest and two in the reforested area. Rhizosphere and root samples were collected during two periods of the year corresponding to the rainy and dry seasons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
30
0
8

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 1 publication
7
30
0
8
Order By: Relevance
“…Although these data might be overestimated, due to the possible inclusion of non-infective and dead spores in the count, the comparison among sites is still valid. In contrast to Moreira-Souza et al (2003) and Moreira et al (2007a), but in agreement with Moreira et al (2006), we found greater spore abundance in the Araucaria reforestation than in the native forest. These contrasting observations are probably related to historical and structural differences between the examined forests.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Although these data might be overestimated, due to the possible inclusion of non-infective and dead spores in the count, the comparison among sites is still valid. In contrast to Moreira-Souza et al (2003) and Moreira et al (2007a), but in agreement with Moreira et al (2006), we found greater spore abundance in the Araucaria reforestation than in the native forest. These contrasting observations are probably related to historical and structural differences between the examined forests.…”
Section: Resultssupporting
confidence: 76%
“…Ten years later, Breuninger et al (2000) compared the richness of species between an area of Araucaria forest and an adjacent grassland in the northern highlands of Rio Grande do Sul, and found a two-fold difference in the number of species of AM fungi: 13 in the former and six in the latter. When comparing a native forest with Araucaria and a reforested area with both Araucaria and Pinus in the State of São Paulo, Moreira-Souza et al (2003) found a greater number of AMF spores in the native forest (21 species) than in the reforested area (14 species). Recently, Moreira et al (2007b) found 25 AMF species three Araucaria ecosystems: a native forest (15 species), an Araucaria reforestation (13 species) and a burned Araucaria reforestation (13 species).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Until now, most surveys described AMF communities present in natural or in agricultural fields using molecular and morphological approaches, on either mycorrhizal roots (Alguacil et al 2009;Verbruggen et al2010) or spores (Moreira-Souza et al 2003;Oehl et al 2003), but just a handful of studies have considered the entire soil, or at least the entire topsoil (Hempel et al 2007;Pivato et al 2007;Cesaro et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Wide distribution and a strong capacity of sporulation usually exist concurrently in dominant species [30,31]. But in this study, the dominant species of G.aggregatum, G. fasiculatum, G.mosseae were found to be widely distributed in root samples rather than their abundance in soil.…”
Section: Discussionmentioning
confidence: 52%